DesainPengembangan Buku Panduan Penyusunan Rencana Pelaksanaan Pembelajaran (RPP) yang Terintegrasi Kecakapan Abad 21 - Darmanella Dian Eka Wati; Ratih Komala Dewi; Chairul Amri (Pendidikan Biologi FKIP UMMY, 2023)
The results of the assessment of learning activities in the Biology learning program development course in odd semesters of the 2016-2017 school year show that students often have difficulties in learning implementation plans, some of the difficulties experienced by students such as difficulties in compiling competency achievement indicators, identifying models or methods that are suitable for learning materials, and apply models or methods in learning activities. The various challenges faced by students in preparing lesson plans were also accompanied by various changes that occurred in the 2013 curriculum. The results of the 2013 curriculum study in 2017 combined Strengthening Character Education, Literacy, 21st Century Skills which is termed 4C (Creative, Critical thinking, Communicative, and Collaborative), and HOTS (Higher Order Thinking Skill) in the teacher planning process. Based on that, I conducted research on Design Development Guidebooks for Developing Learning Implementation Plans Integrated with 21st Century Skills. This research included qualitative research which was analyzed descriptively. The results of this study are in the form of an initial design product of the guidebook which consists of 3 components including: 1) Introduction, this section contains the background, objectives, scope and method of using the guidebook; 2) Learning Activities, consisting of 10 learning activities, each of which contains learning outcomes, material descriptions, assignments/exercise and summaries; 3) Cover.